PENGARUH HARGA DAN KEPUASAN KONSUMEN TERHADAP PENJUALAN PADA AA CATERING - Aminar Sutra Dewi; Yudia Manila Sari (LP2M Universitas Bina Bangsa, 2022)
The purpose of this research is to test price against sales. to test consumer sales against sales. This research was conducted at AA Catering. The type of research used in this research is quantitative research. And the object taken in this research is AA Catering Padang. By using primary and secondary data. The sampling method used the Slovin formula as many as 80 respondents. Data analysis techniques used are validity, reliability, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis, and t test. . The results showed that the price had a positive and significant effect on sales at AA Catering. And consumer satisfaction has a positive and significant effect on sales at AA Catering